The Influence of Cost Perception and Financial Capability on the Intention to Register for Hajj: Evidence from South Jakarta, Indonesia - Nur Rahma Zakiyah; Ahmad Maulidizen; Abdurrahman Faqih (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The increasing cost of Hajj in Indonesia has become an important issue that may influence Muslims' intention to register for the pilgrimage. In recent years, adjustments to Hajj costs have been implemented by the Government of Indonesia and the Indonesian Hajj Financial Management Agency (BPKH) to ensure the long-term sustainability of Hajj financing. While these policies are essential for maintaining financial stability, they may also alter public perceptions regarding Hajj affordability and affect individuals' willingness to register. In addition, financial capability is considered an important factor influencing prospective pilgrims' readiness to fulfill the financial requirements for Hajj. This study aims to examine the influence of cost perception and financial capability on the intention to register for Hajj among Muslim communities in South Jakarta, Indonesia. A quantitative research design with a cross-sectional survey was employed. Data were collected from 100 Muslim respondents residing in South Jakarta who had not previously performed Hajj through a structured questionnaire. The collected data were analyzed using descriptive statistics, validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The findings reveal that cost perception has a positive and statistically significant effect on Hajj registration intention. Financial capability also demonstrates a positive and significant influence on individuals' intention to register for Hajj. Furthermore, both variables jointly exert a significant effect on Hajj registration intention, explaining 29.0% of the variance in the dependent variable (R² = 0.290). These findings suggest that financial considerations remain important determinants of Hajj registration decisions, although other psychological, social, and institutional factors also contribute to individuals' intentions.